Dependent Competing Failure Modeling for the GIL Subject to Partial Discharge and Air Leakage With Random Degradation Initiation Time - Hao, Songhua; Yang, Jun (IEEE transactions on reliability, 2019)
Confronted with the ever-growing demand for electricity delivery over long distances, the gas insulated transmission line (GIL), as an advanced underground technology, has been under rapid development recently. Physics-of-failure analysis for the GIL indicates that it experiences two competing failure modes: 1) Once the amount of air leakage is greater than a predetermined threshold level, a deterioration-based soft failure happens. 2) The arrival of a partial discharge with overlarge voltage will result in a shock-based hard failure. Furthermore, statistical analysis of some engineering projects shows that the beginning of the GIL degradation, i.e., the inner air begins to leak, occurs after an initiation time. In addition, the flashover voltage decreases considerably as the SF6 in the GIL leaks outside and the moisture penetrates inside, which reflects that the hard failure threshold level is related to the degradation process. Confronted with these problems, a new dependent competing failure model is presented for the GIL, with the consideration of degradation initiation time. The GIL reliability assessment is obtained through theoretical derivation, and the numerical calculation method with controllable approximation accuracy. Finally, a case study is carried out to show the implementation of the proposed model.